Kelayakan Instrumen Evaluasi Buku Sekolah Elektronik (BSE) Bahasa Indonesia Siswa SMA Kelas XI - Fernanda Yusi Listeani; Imam Safi'i; Nini Ibrahim (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
Curriculum development is directed at the condition of society in shaping the younger generation. The development of the curriculum also has implications for textbooks. Textbooks are an element of supporting educational facilities and infrastructure. This study aims to describe the feasibility of the Evaluation Instrument in the Indonesian Electronic School Book for SMA class XI students of the 2017 revision of the 2013 Curriculum. This research uses a qualitative approach with the method of Content Analysis. Data collection techniques are using literature study techniques and document techniques. The sample of this research was carried out purposively by determining the criteria according to the research objectives. The sample of this research is an evaluation instrument in the Indonesian language BSE of high school students class XI 2013 revision of the 2017 Curriculum. The data of this research are the feasibility of the evaluation instrument in terms of material aspects and language aspects. The percentage of eligibility level is done by dividing the number of scores obtained by the number of total criteria score then multiplied by one hundred. The results showed that the feasibility of the evaluation instrument in terms of the material aspect was 78.8% and in terms of the language aspect was 84.7%. Based on the research results of the BSE Indonesian evaluation instrument, Class XI high school students are categorized as feasible but must be accompanied by other learning resources. Such as the Internet, Print Media, etc. The results of this study can be used as one of the foundations for teachers to study and consider student textbooks, especially the feasibility of evaluation instruments.